Psychological Mechanisms of Employee Engagement: The Mediating Role of Job Satisfaction in the Relationship between Participative Leadership, Work–Life Balance, and the Work Environment in Cooperatives - Maria Goreti Ilmiana Anapah; Mochammad Al Musadieq; Ika Ruhana (Business and Applied Management Journal, 2026)
Research on employee engagement in cooperative organisations remains relatively limited, even though cooperatives possess unique characteristics whereby employees act as both workers and members of the organisation. Furthermore, the relationship between the influence of participatory leadership, work–life balance, the work environment and job satisfaction on employee engagement still shows empirical inconsistencies across various organisational contexts. Therefore, this study aims to analyse the influence of participatory leadership, work–life balance, and the work environment on employee engagement through the mediation of job satisfaction. This study was conducted at KSP Kopdit Swasti Sari using a quantitative approach with saturated sampling of 71 permanent employees and analysed using SEM-PLS via SmartPLS 4.0. The results indicate that participatory leadership is the strongest predictor of job satisfaction and employee engagement, whilst job satisfaction was found to mediate the effects of participatory leadership, work–life balance, and the work environment on employee engagement. The research model explains 63.7% of the variance in employee engagement. This study contributes by extending the application of the Stimulus-Organism-Response Theory to the context of cooperatives and by confirming the role of job satisfaction as a psychological mechanism linking organisational stimuli to employee engagement.